2018
DOI: 10.4014/jmb.1712.12017
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Potential of Rhodococcus Biodegradative Pathways

Abstract: The genus Rhodococcus is a phylogenetically and catabolically diverse group that has been isolated from diverse environments, including polar and alpine regions, for its versatile ability to degrade a wide variety of natural and synthetic organic compounds. Their metabolic capacity and diversity result from their diverse catabolic genes, which are believed to be obtained through frequent recombination events mediated by large catabolic plasmids. Many rhodococci have been used commercially for the biodegradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 63 publications
0
47
0
3
Order By: Relevance
“…Rhodococcus genus is also a conditional pathogen, which has strong infection ability under specific conditions. It has been reported that Rhodococcus genus is related to the case of human immune dysfunction ( Kim et al., 2018 ). In summary, there were more bacteria that can inhibit host energy absorption and benefit intestinal health in the ileum of the group without hepatic steatosis, whereas there were more conditional pathogens or harmful bacteria in the ileum of the group with hepatic steatosis.…”
Section: Resultsmentioning
confidence: 99%
“…Rhodococcus genus is also a conditional pathogen, which has strong infection ability under specific conditions. It has been reported that Rhodococcus genus is related to the case of human immune dysfunction ( Kim et al., 2018 ). In summary, there were more bacteria that can inhibit host energy absorption and benefit intestinal health in the ileum of the group without hepatic steatosis, whereas there were more conditional pathogens or harmful bacteria in the ileum of the group with hepatic steatosis.…”
Section: Resultsmentioning
confidence: 99%
“…M embers of the Rhodococcus genus are aerobic, GC-rich, Gram-positive bacteria belonging to the actinomycetes (1), whose recognized capacity to degrade hydrocarbons suggests that they might be useful in lignin biodegradation (2)(3)(4)(5). Here, we report the complete genome sequence of Rhodococcus ruber R1, an actinobacterium with the ability to grow on several phenolics as the sole carbon source (Fig.…”
mentioning
confidence: 94%
“…Rhodococcus is a genus of a gram‐positive bacteria that has been described to host a variety of enzymes and degradation pathways with high potential for the use in industrial processes . Its metabolic diversity often stems from large, linear plasmids that carry the protein‐encoding genes for degradative enzyme systems . Abundant horizontal gene‐transfer events occurring via these linear plasmids as well as a high multiplicity of catabolic enzymes contributed to the catabolic versatility of Rhodococcus genus members …”
Section: Introductionmentioning
confidence: 99%
“…[8,14] Its metabolic diversity often stems from large, linear plasmids that carry the protein-encoding genes for degradative enzyme systems. [15] Abundant horizontal genetransfer events occurring via these linear plasmids as well as a high multiplicity of catabolic enzymes contributed to the catabolic versatility of Rhodococcus genus members. [15][16][17] To study the described water addition in-depth, the identification and isolation of the responsible enzyme were first aimed for.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation